(untitled) (International Journal of Food and Nutritional Sciences, 2023)
A study examining the use of information technology (IT) in Kendriya Vidyalaya libraries would likely focus on several key areas: the integration of IT into library operations, the impact of IT on library resources and services, user satisfaction with IT-enabled services, and challenges and opportunities in utilizing IT effectively. Libraries in these schools are increasingly leveraging IT for automation, digital resources, and enhancing the overall learning experience